Faktor-Faktor yang Mempengaruhi Kepuasan Konsumen Kedai “Pesenkopi” di Kota Malang - Siti Saniah; Bambang Yudi Ariadi; Harpowo Harpowo (Agriecobis : Journal of Agricultural Socioeconomics and Business, 2020)
The purpose of this study are as follows: 1. To find out the quality of products to consumers satisfaction Pesen Kopi Malang 2. To find out the brand of consumer satisfaction Pesen Kopi Malang 3. To find out loyalty to consumers satisfaction Pesen Kopi Malang. This research was conducted at Malang Coffee Pesen Coffee Shop in January-February 2020. The type of data used in this study is quantitative data obtained from the distribution of questionnaires. The sampling technique is using accidental sampling. Sampling amounted to 75 respondents. Data collection techniques are primary data and documentation. Data analysis methods used were validity and reliability tests, to analyze the PLS Warp. The results of the path coefficients and P values on customer satisfaction are only variables X3 (loyalty) which are significant, that is <0.001 <0.05 and X1 (product quality), X2 (brand) is not significant.